Pelatihan peremajaan kakao berbasis grafting pada petani Mujir Aibone Ransiki Manokwari Selatan: Grafting-based cocoa rejuvenation training For Mujir Aibone Farmers In Ransiki Manokwari - Suparno, Antonius; Parari, Trisday; Prabawardani, Saraswati; Sutiharni , Sutiharni; Mawikere, Nouke L.; Daeng, Baso; Noya, Alce I.; Purbokurniawan, Purbokurniawan; Paisey, Elda K.; Ningsi, Ratna; Wibawati, Zarima; Nurlailah, Nurlailah; Dare, Darius; Febrianto, Sudi; Litaay, Gabriella (Fakultas Peternakan Universitas Papua, 2026)
ABSTRACT Cocoa (Theobroma cacao L.) is an important plantation commodity in Indonesia, including West Papua, but its productivity at smallholder level remains low due to suboptimal crop management, use of low-performing planting materials, and aging trees. This community service program aimed to improve farmers' capacity to rejuvenate old cocoa stands through grafting techniques. The activity was conducted on July 17, 2025, in the cocoa field of a member of the Mujir Aibone farmer group, Ransiki, South Manokwari Regency, and implemented through short lectures, field demonstrations, and supervised hands-on practice of side and top grafting. The results showed high participation and strong enthusiasm among farmers, most of whom had no prior experience with grafting. Follow-up evaluation two weeks after training indicated an average grafting success rate of 80%, suggesting that this technique is feasible and promising for accelerating cocoa rejuvenation and supporting productivity improvement in smallholder plantations. Keywords: Cocoa; Grafting; Productivity; Rejuvenation; Training ABSTRAK Tanaman kakao (Theobroma cacao L.) merupakan komoditas perkebunan penting di dunia maupun Indonesia, termasuk Papua. Namun, produktivitas kakao rakyat masih relatif rendah akibat teknik budidaya yang belum optimal, penggunaan bahan tanam nonunggul, serta dominasi tanaman tua yang telah melewati masa produktif. Salah satu solusi yang dapat diterapkan adalah peremajaan melalui teknik grafting dengan memanfaatkan entres dari varietas atau klon unggul nasional. Kegiatan ini bertujuan meningkatkan pengetahuan dan keterampilan petani dalam menerapkan sambung samping dan sambung pucuk pada tanaman kakao dewasa untuk mempercepat peremajaan kebun. Metode pelaksanaan meliputi ceramah singkat, demonstrasi lapang, dan praktik langsung di kebun petani. Kegiatan dilaksanakan pada 17 Juli 2025 di kebun anggota Kelompok Tani Mujir Aibone, Ransiki, Kabupaten Manokwari Selatan, Provinsi Papua Barat. Hasil pengabdian menunjukkan minat dan partisipasi petani yang tinggi, serta peningkatan kemampuan peserta dalam mempraktikkan teknik sambung samping dan sambung pucuk. Kata kunci: Grafting; Kakao; Pelatihan; Peremajaan; Produktivitas